On Pseudospherical Surfaces in E4 with Grassmann Image of Prescribed Type - Gorkavyy, Vasyl (Журнал математичної фізики, аналізу, геометрії, 2006)
It is demonstrated that there exist surfaces of constant negative Gauss curvature in E^4 whose Grassmann image consists of either hyperbolic or parabolic or elliptic points. As a consequence, there exist surfaces of constant negative Gauss curvature in E^4 which do not admit Backlund transformations with help of pseudospherical congruencies. A geometric representation for pseudospherical surfaces in E^4 with parabolic Grassmann image is proposed. Mathematics Subject Classification: 53A07, 53A25, 53B25.